Investigating the relationship between happiness and self-esteem with self-efficacy in the clinical performance of midwives working in medical centers and comprehensive health services - Zahra Mohebbi-Dehnavi; Mahnaz Noroozi (Journal of Education and Health Promotion)
BACKGROUND: Self-efficacy is one of the factors affecting correct performance, especially in emergency and stressful situations. The mental state of people can affect their performance. The present study was conducted with the aim of determining the relationship between self-esteem and happiness with self-efficacy in the clinical practice of midwives working in medical centers and comprehensive health services in Isfahan city. MATERIALS AND METHODS: The present study was a quantitative correlational study that was carried out using a quota method on 200 midwives working in health centers and comprehensive health services in Isfahan in 2021–2022. The tools used in this research were happiness, self-esteem, and self-efficacy questionnaires in clinical practice. The collected data were analyzed by descriptive statistics and Pearson’s correlation coefficient test. RESULTS: The results showed that the average clinical performance self-efficacy score in midwives was 24.15 ± 109.02, the average happiness score was 14.95 ± 65.32, and the average self-esteem score was 24.40 ± 1.52. There is a significant relationship between the overall clinical performance self-efficacy score and both variables of happiness (P = 0.001, r = 0.03) and self-esteem (P = 0.04, r = 0.091). CONCLUSION: According to the results of this study, paying attention to the happiness and self-esteem of midwives and promoting them can improve their efficiency and performance and ultimately improve the health of mothers and babies and then the society.